2016
DOI: 10.1016/j.jchf.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Novel Long-Acting GLP-1 Agonist, Albiglutide, on Cardiac Function, Cardiac Metabolism, and Exercise Capacity in Patients With Chronic Heart Failure and Reduced Ejection Fraction

Abstract: Although there was no detectable effect of albiglutide on cardiac function or myocardial glucose use, there was a modest increase in peak oxygen consumption, which could have been mediated by noncardiac effects. (A Multi-center, Placebo-controlled Study to Evaluate the Safety of GSK716155 and Its Effects on Myocardial Metabolism, Myocardial Function, and Exercise Capacity in Patients With NYHA Class II/III Congestive Heart Failure; NCT01357850).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 24 publications
1
81
0
7
Order By: Relevance
“…Findings of reduced numbers of total (fatal and nonfatal) MIs reported in liraglutide-treated subjects in LEADER (21) has heightened interest in identification of mechanisms linking GLP-1R signaling to ischemic cardioprotection. Although some studies demonstrate that GLP-1R agonism directly modulates cardiac fuel metabolism in normal or dysfunctional hearts from human subjects with or without T2D, the existing human data are inconclusive (58,59), and limited information is available regarding whether and how GLP-1 alters myocardial fuel metabolism in the ischemic or failing human heart. The accumulated evidence suggests that the GLP-1R is predominantly expressed in atria, and not ventricles, in hearts from mice and rats (3), indirectly localized via reporter gene expression to atrial cardiomyocytes and VSMs in mouse ventricle (34).…”
Section: Direct Glp-1 Action In the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of reduced numbers of total (fatal and nonfatal) MIs reported in liraglutide-treated subjects in LEADER (21) has heightened interest in identification of mechanisms linking GLP-1R signaling to ischemic cardioprotection. Although some studies demonstrate that GLP-1R agonism directly modulates cardiac fuel metabolism in normal or dysfunctional hearts from human subjects with or without T2D, the existing human data are inconclusive (58,59), and limited information is available regarding whether and how GLP-1 alters myocardial fuel metabolism in the ischemic or failing human heart. The accumulated evidence suggests that the GLP-1R is predominantly expressed in atria, and not ventricles, in hearts from mice and rats (3), indirectly localized via reporter gene expression to atrial cardiomyocytes and VSMs in mouse ventricle (34).…”
Section: Direct Glp-1 Action In the Heartmentioning
confidence: 99%
“…Reassuringly, no heart failure-related adverse outcomes were detected in studies examining the safety of GLP-1R agonists in the Evaluation of Lixisenatide in Acute Coronary Syndrome (ELIXA), LEADER, Trial to Evaluate Cardiovascular and Other Long-term Outcomes With Semaglutide in Subjects With Type 2 Diabetes (SUSTAIN-6), or EXSCEL (18-21), which collectively enrolled thousands of subjects with mild to moderate heart failure. Nevertheless, three smaller dedicated studies of more advanced heart failure, two with liraglutide (24 weeks) and one with albiglutide (12 weeks), failed to demonstrate functional improvement in human subjects, with or without T2D, with reduced ejection fraction and a history of hospitalization for heart failure (59,63,64). Indeed, rehospitalization for heart failure was numerically more common with liraglutide (63), and increased reports of arrhythmias, including supraventricular tachycardia, were noted in liraglutide-treated subjects in these trials (63,64), consistent with the localization of GLP-1R expression to the sinoatrial node.…”
Section: Heart Failurementioning
confidence: 99%
“…LePore et al [19] looked at the effects of 12 weeks of treatment of albiglutide, a long acting GLP -1 agonist in patients with stable, chronic heart failure with reduced LV EF <40% and NYHA functional class II to III symptoms. A 30mg dose was compared with placebo in 81 randomized patients.…”
Section: The Results Of Randomized Clinical Trialsmentioning
confidence: 99%
“…In addition, a recent study performed in T2D patients with HF (New York Heart Association II or III) and LVEF < 40% showed that treatment with the new GLP-1RA albiglutide (30 mg once a week for 12 weeks) compared with a placebo did not significantly improve LVEF, the 6-min walk test, or myocardial glucose or oxygen use [32].…”
Section: Glp-1 and Cardiac Functionmentioning
confidence: 99%